Intracranial self-stimulation mitigates spatial task deficits, modifies miR-146a and miR-495 serum levels and restores hippocampal NRF2 levels in a rat model of sporadic Alzheimer’s disease - Riberas-Sánchez, Andrea; García-Brito, Soleil; Vila-Solés, Laia; Aldavert-Vera, Laura; Segura-Torres, Pilar; Huguet, Gemma; Carreras-Badosa, Gemma; Kádár, Elisabet (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) is the most prevalent neurodegenerative disease associated with aging. While deep brain stimulation (DBS) shows therapeutic promise, the long-term persistence of its effects remains understudied. Expression patterns of circulating miRNAs, proposed diagnostic biomarkers, and their modulation by DBS are still poorly characterized in longitudinal studies. This study investigates the effect of a 13-week prolonged ICSS treatment on spatial memory and serum miRNA expression in a male rat model of sporadic AD (SAD) by intracerebroventricular injection of streptozotocin (STZ).MethodsMorris water maze (MWM) tasks were conducted at 1 and 5 months post-STZ. Serum miRNA levels were quantified by qRT-PCR at 29 (Ser0), 73 (Ser1) and 136 (Ser2) days after STZ administration. Corpus callosum thickness and NRF2 protein levels in the hippocampal CA1 region were assessed using Nissl staining and immunohistochemistry, respectively. Target validation of miR-495 was performed via transfection assays in the human neuroblastoma SH-SY5Y cell line.ResultsMFB-ICSS treatment significantly reduced escape latency in the MWM task in the STZ + ICSS group compared to untreated STZ rats at 5 months post-STZ. At Ser0, levels of miR-16, miR-30c, miR-181, miR-191 and miR-196a were significantly increased in STZ group. In STZ rats, miR-146a and miR-495 levels increased from Ser1 to Ser2, an effect not observed in the Control or STZ + ICSS groups. In SH-SY5Y cells, miR-495 overexpression significantly downregulated both NRF2 mRNA and protein levels. Moreover, STZ exposure increased miR-495 and reduced NRF2 protein levels. MFB-ICSS also reversed the STZ-induced reductions in both CA1 NRF2 levels and corpus callosum thickness.ConclusionProlonged MFB-ICSS treatment mitigates cognitive deficits, modulates circulating levels of miRNA-495 and miR-146a, restores hippocampal NRF2 levels, and preserves corpus callosum integrity in the SAD rat model by STZ injection. These findings highlight the therapeutic potential of MFB-ICSS as a non-pharmacological intervention in AD. Furthermore, this study confirms NRF2 as a target of miR-495 in the context of AD.